Ethical Issues in Rehabilitation Medicine (Mugda Medical College Journal, 2024)
Within the past few decades, there has been a tremendous increase in the knowledge and awareness of ethical issues and dilemmas within the medical profession. However, until more recently, the problems of chronic illness, and more specifically of rehabilitation-related issues, have received relatively little attention. We reviewed a large amount of literature concerning various ethical dilemmas that occur specifically within the context of chronic care and rehabilitation medicine. The review was done through extensive searching of databases between January and June of 2018. The search was confined to Google Scholar, HINARI, and PubMed published articles. Besides, some institutional guidelines were taken into consideration. Keywords used for searching were ‘rehabilitation’, ‘rehabilitation medicine’, ‘chronic disease’, ‘chronic illness’, ‘disability’, ‘ethics’, ‘ethical issues’, and ‘ethical dilemma’. After meticulous scrutiny, a total of 21 journal articles and 3 guidelines were selected for this review. The goal of this review is to provide a brief overview of the major ethical principles as well as some specific examples of ethical issues that might be encountered on a day-to-day basis by rehabilitation practitioners.Mugda Med Coll J. 2023; 6(2): 93-98